Examination of the extent of elder abuse in Western Australia - Blundell, Barbara; Clare, M.; Clare, J. (Crime Research Centre, The University of Western Australia, 2011)
This study examines elder abuse in Western Australia, including its scope and the capacity of agencies to address it. Twenty-six professionals from ten organisations that respond to elder abuse in Western Australia were interviewed. Two focus groups were conducted with ten representatives from allied agencies. De-identified quantitative data from five agencies was also examined. Data collection commenced in May 2010 and concluded in December 2010. Quantitative data showed indications of an overall trend for an increased volume of elder abuse cases. Across all data sources, financial abuse was the most common type of abuse, followed by neglect and psychological abuse. The definition of elder abuse is problematic and requires further exploration. A cohesive approach to elder abuse is required across government and non-government organisations. Elder abuse lags behind child abuse and domestic violence in terms of public recognition and social responses.